Multiparametrische MRT der Prostata zum Therapiemonitoring nach Strahlentherapie - Weidner, Anja; Dinter, Dietmar; Bohrer, Markus; Sertdemir, Metin; Hausmann, Daniel; Wenz, Frederik; Schönberg, Stefan (Der Radiologe, 2012)
Clinical/methodical issueRadiation therapy is a therapeutic option with curative intent for patients with prostate cancer. Monitoring of prostate-specific antigen (PSA) values is the current standard of care in the follow-up. Imaging is recommended only for symptomatic patients and/or for further therapeutic options.Standard radiological methodsFor detection of local recurrence magnetic resonance imaging (MRI) of the prostate is acknowledged as the method of choice.PerformanceGood results for primary diagnosis were found especially in combination with functional techniques, whereas in recurrent prostate cancer only few studies with heterogeneous study design are available for prostate MRI. Furthermore, changes in different MRI modalities due to radiation therapy have been insufficiently investigated to date.Practical recommendationsAs the initial results were promising prostate MRI and available therapeutic options for detection of local recurrence should be considered in patients with increased PSA.
Gesehen am 02.05.2019